Biometric key generation based on generated intervals and two-layer error correcting technique. (March 2021) - Wang, Peiyi; You, Lin; Hu, Gengran; Hu, Liqin; Jian, Zhihua; Xing, Chaoping
Highlights: The bio-key is generated based on the feature distances between the minutiae and it will ensure a better security of the fingerprint data or template. The generated intervals can decrease the influence of the fingerprint intra-variation and improve the bio-key regeneration rate. The codewords obtained from the encoding of the generated intervals can implement the cancellability of the bio-key. The generated bio-key by our approach can be updated by changing the interval codewords. The two-layer error correction technique can detect and correct the random or unexpected errors and it will improve the reliability of the bio-key. Our bio-key generation approach has been practically experimented. Abstract: As for a biometric key, key management and biometric data security are both important. Existing bio-key generation methods are usually based on the biometric templates or features directly, it may expose user's biometric data and will further make the biometric data permanently unusable for his secure identification recognitions. In this paper, a fingerprint bio-key generation approach using the feature distance is proposed. We utilize the relative distances among user's fingerprint minutiae to generate a unique bio-key. Such bio-key is determinable and recoverable via the generation interval scheme. In addition, we use a two-layer error correcting technique to guarantee a better reliability during the data transmission. The experimental results positively show that our approach can ensure higher security of the bio-key and guarantee a good key regeneration rate. Besides, the storage of the original bio-key or any fingerprint template is unnecessary.